Clinical and Molecular Allergy - Maggi, Enrico; Incorvaia, Cristoforo
Clinical and Molecular Allergy is an open access, peer-reviewed, international journal that covers all aspects of allergy research with a primary focus on molecular allergy and clinical applications of molecular techniques. Clinical and Molecular Allergy is the official journal of the Italian Society of Allergology, Asthma and Clinical Immunology. This international journal appeals to allergists & immunologists, pulmonologists, otolaryngologists, geneticists and other physicians, healthcare workers, medical students and the public worldwide. Topics of interest include, but are not limited to: Clinical allergy, including respiratory allergy, food allergy, drug allergy, insect sting allergy Diagnostics (component resolved diagnostics, allergen extract diagnostics) Structural biology of allergens (and their interactions with the immune system) Bioinformatics of allergens Epitopes and mimotopes Genetics and epigenetics Therapeutics using molecular techniques Effect of the microbiome on development of allergic disease The journal accepts research articles, reviews, commentaries, case reports and correspondence and has six different sections: Allergen Immunotherapy Biologicals Clinical and Molecular Allergy Clinical Immunology Food, Drug, Insect Allergy Respiratory Allergy.